Comparing the taxonomic and functional profiles of gut microbiota from three pig breeds by metagenomic sequencing - Xu, Taojie; Sun, Haichao; Yi, Lanlan; Yang, Minghua; Zhu, Junhong; Huang, Ying; Pan, Hongbin; Li, Honghui; Li, Weizhen; Zhao, Hongye; Wei, Hongjiang; Zhao, Sumei (Frontiers in Genetics, 2022)
To investigate the difference of microbial communities among Diannan small-ear (DNSE), Dahe black (DHB) and Yorkshire (YS) pigs, we compared the microbial taxonomic and functional composition using a metagenomic approach. A total of 1,002,362 non-redundant microbial genes were identified, DHB and YS pigs had more similar genetic makeup compared with DNSE pigs. Bacteroidetes, Firmicutes and Spirochetes were the three most abundant phyla for all pig breeds, and DNSE pigs had a higher abundance of Prevotella genus than DHB and YS pigs. The functional profiles varied among the three pig breeds, DNSE pigs had more active carbohydrate metabolism and more abundant antibiotic resistance genes than the other two pig breeds. Moreover, we found that peptide and macrolide resistances genes in DNSE pigs were more abundant than that in DHB pigs (p < 0.05). This study will help to provide a theoretical basis for the development of native pig breeds in Yunnan Province, China.